Caso de estudio: Análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Cochachi Malpica, Rocio Guadalupe (2019)
This document sets out a strategic plan for The Holding of Camposol. For a better analysis, the work is divided into four chapters where evaluated and proposed strategies that allows keep the leadership of this company. It is important to note that in these more than twenty years operating the capacity of innovation and development the products have allowed to Camposol been worldwide recognized. In the first chapter through tools such as the business model canvas, the value chain, the PEST analysis and Porter’s five forces are made an internal and external diagnostic. Then, in the second part using the IFE & EFE matrix and the vector SWOT it was possible to identify and formulate strategies. In this stage is also analyzed the vision, mission, principles and objectives of the corporation, from it is possible to suggest changes for the Strategic Business Units. In the third segment it is analyze the organizational structure and it presents the global, corporate, business and functional strategies. Finally, in order to communicate effectively and clearly the strategic, with the Balanced Scorecard and the Integral Control board it is possible to link the objectives and the company strategy in a cause-effect relationship.